(untitled) (Al-Mansour Journal, 2025)
Image transmission can be secured effectively, ensuring confidentiality, integrity, and authenticity of the transmitted image data by applying encryption process. IoT systems required lightweight method to satisfy the limitation in the resources. In this paper a hybrid lightweight encryption method that combining SPECK and RC5 algorithms is proposed with a method for self key establishing. The essential to implement secure key management practices and use robust transmission protocols to mitigate security risks and vulnerabilities. Security and speed have been achieved to encryption/decryption color images of different sizes and different kernels based on the number of kernels selected. It is carried out in four rounds, where the output of one of the two algorithms is RC5 Input for the present algorithm is executed four rounds, the outputs of the present algorithm are swapped with the outputs of the second algorithm, RC5, and merge them to obtain the final encryption output. The keys of these algorithms are generated using the Six-dimensional chaos system equation.